2018
DOI: 10.1080/15592294.2018.1549462
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA methylation in human trophoblast differentiation

Abstract: The placenta is a vital fetal exchange organ connecting mother and baby. Specialised placental epithelial cells, called trophoblasts, are essential for adequate placental function. Trophoblasts transform the maternal vasculature to allow efficient blood flow to the placenta and facilitate adequate nutrient uptake. Placental development is in part regulated by epigenetic mechanisms. However, our understanding of how DNA methylation contributes to human trophoblast differentiation is limited. To better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 104 publications
3
33
0
Order By: Relevance
“…A recent study has addressed this question using a side-population trophoblasts, a candidate human TSC [55], isolated from first trimester placenta. The comparison of the methylomes of this side-population trophoblasts and the methylomes of vCTs and EVTs all isolated from the same first trimester placenta, showed that each population had a distinctive methylome [56]. In comparison to mature vCTs, side-population trophoblasts, showed differential methylation of genes and miRNAs involved in cell cycle regulation, differentiation and regulation of pluripotency.…”
Section: Epigenetics and Normal Placental Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has addressed this question using a side-population trophoblasts, a candidate human TSC [55], isolated from first trimester placenta. The comparison of the methylomes of this side-population trophoblasts and the methylomes of vCTs and EVTs all isolated from the same first trimester placenta, showed that each population had a distinctive methylome [56]. In comparison to mature vCTs, side-population trophoblasts, showed differential methylation of genes and miRNAs involved in cell cycle regulation, differentiation and regulation of pluripotency.…”
Section: Epigenetics and Normal Placental Developmentmentioning
confidence: 99%
“…This has also been analyzed by genome-scale DNA methylation analysis. Gamage and coworkers have analyzed by RRBS side population trophoblasts, CTs and EVTs from human first trimester placentas [56]. Forty-one genes involved in EMT and metastatic cancer pathways were found methylated between CT and EVTs, possibly contributing to the invasive phenotype of these cells.…”
Section: Epigenetic Alterations In Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a comprehensive analysis of DNAm for human placental cell types using the Illumina EPIC methylation array. Previous placental cell DNAm studies have focused on a lesser number of cell types (41), used lower resolution approaches (42), or focused on a narrow gestational age range (e.g. only rst trimester, or only term).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships we found for repetitive elements and global DNAm between cell types and CV were also largely consistent in our rst trimester samples (Additional File 7: Table S8, Additional File 1: Figure S11B). To determine genome-wide repetitive element DNAm, we used the random forest -based 'REMP' algorithm (41) to predict 438,664 Alu CpGs and 39,136 LINE1 CpGs that are not covered by the EPIC array. Relationships between cell types and CV for predicted and non-predicted repetitive elements were mostly the same, except TB DNAm in predicted Alu and LINE1 CpGs was not signi cantly different compared to CV (Additional File 7: Table S8, Additional File 1: Figure S11C).…”
Section: Dna Methylation Characterization Of Syncytiotrophoblast and mentioning
confidence: 99%